Implications of the Contract Freedom Principle and Legal Consequences of Standard Contract Which Detrimental to Debtors of Bank Syariah Indonesia (BSI) Makassar - Danil Danil; Asbullah Thamrin; Ilham Ilham; Muhammad Obie (Pascasarjana IAIN Sultan Amai Gorontalo, 2022)
The objectives of the study were as follows: 1) To determine how the freedom of contract principle is affected by the implementation of standard contracts; and 2) To determine the legal repercussions of standard contracts whose terms are unfavorable to the debtor or consumer. This kind of research consisted of normative legal research or research conducted in libraries. The study made use of qualitative analysis by elaborating on the previously collected data through the use of words or statements. 1) The implication of the principle of freedom of contract in the implementation of a standard contract is first determined as a written condition in a form, then duplicated in a certain amount according to need. This was shown to be the case by the findings. Because of the preceding, customers are unable to negotiate the terms of the agreement because these forms are then provided to customers in mass quantities, despite the fact that the conditions outlined on each form are unique from those outlined on the other forms. To phrase it another way, consumers do not have the same level of bargaining power as producers or creditors; 2) The legal consequences of standard contracts whose contents are detrimental to the debtor/consumer because at the beginning of making/composing the agreement the creditor/producer did not involve the customer in making/composing the agreement so that they had no other choice; 3) The As a consequence of this, a number of aspects of the standard agreement are regarded as being in conflict with the rights of the debtor or consumer. These aspects are as follows: (1) The content, terms, and conditions are determined unilaterally; (2) the contents of the agreement are not known about the legal impact and consequences; (3) the bank is more dominant in the agreement; (4) Conditions are forced in the agreement.